Genetic diversity within a newly identified population of Adenophora liliifolia (L.) A.DC. in Romania: implications for conservation - Manole, Anca; Banciu, Cristian; Indreica, Adrian (Marin Dracea National Research-Development Institute in Forestry, 2015)
Adenophora liliifolia is a relict plant species, endangered at European level. Its occurrence in Romania is limited to a very few sites. The amount of genetic diversity of plant species is a valuable indicator of population, being the baseline in developing proper strategies for their conservation. Inter-simple sequence repeats (ISSRs) markers were used to analyze polymorphism in A. liliifolia genome and to evaluate the genetic diversity and accordingly, the state of a recently identified population. Five ISSR primers, specially designed for plants, and containing different simple sequence repeat motifs were tested. A total of 52 ISSR fragments were generated of which 41 were polymorphic (78.84%) and 32 (61.53%) specific to Adenophora genus. The value of Shannon’s index of genotypic diversity was 0.812. Jaccard similarity coefficient was calculated for pair wise comparisons among all individuals and ranged from 0.17 to 0.83. The genetic variability between individuals was 78.84% which suggests a relative high genetic differentiation. Although the level of genetic variability is moderate to high, the population is declining and exposed to demographic stochasticity. A possible cause is species germination requirements hampered by modification in vegetation structure and abundance. The population survival and reinforcement is conditioned by urgent measures for forest management in order to reduce herbaceous and shrubby vegetation and to limit mowing and grazing. Ex situ conservation measures are also proposed.
Keywords: Adenophora liliifolia; ISSR markers; genetic diversity; conservation